Markets and People : Romania Country Economic Memorandum - World Bank (Washington, DC: World Bank, 2020)
Romania’s income per capita has increased from 26 percent of the EU-28 average in 2000 to 63 percent in 2017, but this economic success rests on the wobbly foundations of unfavorable demographics, weak human capital, and ineffective institutions. Going forward, stronger competition and better human capital are critical to increasing the economy’s growth potential. Romanian manufacturing ﬁrms are exposed to domestic and international competition, ensuring the ﬂow of resources and market shares to more efﬁcient players. This has not been the case for services, where anticompetitive regulations and direct state control often limit efﬁciency gains. Romanian state-owned enterprises do not compete on an equal footing with private sector ﬁrms, distorting market outcomes and hampering the efﬁcient allocation of resources. Removal of these restrictions would have a signiﬁcant positive impact on GDP growth. Competitively neutral policies are needed to ensure that all enterprises, public or private, domestic or foreign, face the same set of rules. Romania’s human capital accumulation--proxied by the World Bank’s Human Capital Index (HCI)--is the lowest in the European Union and varies widely across counties. Disparities in education outcomes remain relevant across and within regions of Romania. Learning gaps in primary and secondary education persist. These can be seen clearly between urban and rural areas, across regions, and across social groups, requiring changes both at the systems level and at the learning-center level. In the labor market, the automation of production processes has started driving demand for higher levels of cognitive skills, while jobs involving the routine application of procedural knowledge are shrinking in number. A paradigm shift would require reforms in primary and secondary schooling, in addition to more targeted actions, to establish an effective skills development system to bolster human capital.